Ethnomathematics: A Study of Plane Geometry Concepts at the Walahar Dam - Putri Nur'aini, Jihan; Noor Aini, Indrie; Rosita Dewi Nur, Iyan (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aims to explore ethnomathematical aspects in the Walahar Dam, particularly in identifying plane geometry concepts embedded in its architectural structures. This research employed a descriptive qualitative method. Data were collected through field observations, interviews with dam managers, and documentation. The results show that various plane geometry concepts are found in the Walahar Dam, including triangles, rectangles, trapezoids, circles, semicircles, tessellations, and composite shapes. These geometric forms are not only functional in structural design but also reflect cultural and aesthetic values influenced by Dutch colonial and Chinese architecture. The findings indicate that the Walahar Dam has significant potential as a contextual learning resource in mathematics, especially in teaching plane geometry concepts based on local culture. This study contributes to enriching ethnomathematics literature and supports the integration of cultural heritage into mathematics learning.